Rancang Bangun Alat Deteksi Kadar Kolesterol Dalam Darah Dengan Teknik Non Invasive Berbasis Mikrokontroler Wemos D1 R1 - Yuniar, Noeris; Supriyanto, Amir; Ayu, Humairoh Ratu; Suciyati, Sri Wahyu (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
Cholesterol level checks are generally performed either invasively or using a portable blood test strip. It requires a long laboratory analysis time and causes pain in the body, so a non-invasive tool is needed to check cholesterol levels. The study aims to detect cholesterol levels in the blood with a non-invasive technique based on the Wemos D1 R1 Microcontroller using the DS100A Oximeter Sensor. This tool is equipped with a Liquid Crystal Display (LCD) as a cholesterol level display and an LED light as a cholesterol level indicator that will light up red when cholesterol is high (>=240 mg/dL), light up yellow when cholesterol is at the high limit (200-239 mg/dL), and light up green when cholesterol is normal (<=200 mg/dL). Cholesterol level measurement is done by utilizing the red LED light emission on the sensor attached to the finger. Then, the photodiode will capture the light intensity from the red LED into a voltage value. A 10-bit ADC on the microcontroller then reads the voltage value. The ADC value was then converted into a cholesterol level in milligrams per deciliter (mg/dL) using a linear regression equation. The designed device is capable of detecting cholesterol levels in the range of 150-240 mg/dL. Test results indicate that the non-invasive cholesterol level test device has been successfully developed, with a precision of 98.85% and an error of 1.15%. Accuracy testing yielded a value of 97.14% with an error of 2.86%.